Fiona plays soccer - Cowdrey, Richard; Wu, Donald (2023)
Fiona the hippo and her friends find a soccer ball and decide to play a game.
Keywords: Fiona -- (Hippopotamus), -- 2017- -- Fiction; Soccer -- Fiction; Hippopotamuses -- Fiction; Zoo animals -- Fiction; JUVENILE FICTION / Animals / Zoos; JUVENILE FICTION / Sports & Recreation / Soccer; Animal fiction; Picture books